2013
DOI: 10.1093/her/cyt036
|View full text |Cite
|
Sign up to set email alerts
|

Social motives for drinking in students should not be neglected in efforts to decrease problematic drinking

Abstract: High heavy drinking prevalence persists in students. Recently, drinking motivation received a lot of attention as an important determinant. Enhancement and coping motives are mostly positively related and conformity motives are mostly negatively related with heavy drinking. Relations are less clear for social motives. This study aimed at gaining more insight in the role of drinking motives in heavy drinking students. Overall, 15 897 Belgian university and college students (mean age: 20.7, SD = 2.6) anonymously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 46 publications
7
41
0
2
Order By: Relevance
“…This phenomenon may be related to differences in student inflow and drinking habits in different faculties [30,40]. The observed relationship with social drinking motives is consistent with another Belgian study in higher education, that also found a positive relation with monthly binge drinking [26]. For individual-level perceived norms positive relationships were found for same-and opposite-sex, both in males and females, which is in line with other research [14].…”
Section: This Study Aimed To Investigate Differences In Frequent Bingsupporting
confidence: 91%
See 1 more Smart Citation
“…This phenomenon may be related to differences in student inflow and drinking habits in different faculties [30,40]. The observed relationship with social drinking motives is consistent with another Belgian study in higher education, that also found a positive relation with monthly binge drinking [26]. For individual-level perceived norms positive relationships were found for same-and opposite-sex, both in males and females, which is in line with other research [14].…”
Section: This Study Aimed To Investigate Differences In Frequent Bingsupporting
confidence: 91%
“…When students drink for social drinking motives, they drink to enhance their pleasant feeling with an external trigger, like peers (e.g., to celebrate something with friends, or to be sociable) [24,25]. Social drinking motives are the most prevalent motives in students [23,26], which indicates that drinking alcohol is mainly a social event [1,17]. This social character explains why perceived norms motivate students to drink more often for social reasons, and why perceived norms stronger relate to alcohol use in those students drinking for social motives [21,22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite literature indicating that social motives seem most influential to alcohol consumption (e.g., Damme et al, 2013), the Drunkorexia Motives subscale seems to be most aligned with the conformity concept. In addition, the subscale correlates most strongly with DMQ-R coping and conformity motives scales.…”
Section: Discussionmentioning
confidence: 66%
“…Esto podría explicarse por cuestiones relacionadas con diferencias en la conducta social como parte de los roles de género (Bratberg et al, 2016). Las ocasiones de consumo reducidas, no obstante, fueron la tercera razón en la muestra total, y algunos autores han alertado sobre la importancia de los motivos sociales de consumo en la adopción de patrones de ingesta de alcohol de riesgo, con diferencias según grupos culturales (Van Damme, Maes, Clays, Rosiers, Van Hal, & Hublet, 2013). Para los varones, las razones más prevalentes fueron las relacionadas, si se quiere, con el cuidado de la salud (actividad física y razones médicas).…”
Section: Tabla 3 Razones Para Cambiar El Consumo De Alcohol Según Sexunclassified